Technology Development at the Bedford Institute of Oceanography, 1962-1986 - Murphy, Michael (Scientia Canadensis, 2016)
This paper explores the relationship between technology and discovery in oceanography, examining examples of instrumentation development at the Bedford Institute of Oceanography (BIO). Between 1962 and 1986, BIO researchers and technicians initiated a wave of rapid technological development, while also adopting technology developed elsewhere. These developments were abridge into the digital age as BIO staff incorporated computer hardware and software into instrument development. This paper summarizes these developments, their impact on the work of the Institute, and factors that influenced this work, and how they changed over time BIO emerged as a world-class oceanographic institution.